MAGNETIC FIELD CONTROL IN AN ANALYTIC PLATFORM FOR ASSESSMENT OF PATHOGENIC BACTERIA (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
The paper presents a conceptual, analytical platform with various pathogen detection applications, based on a hybrid magnetic field source, comprised of permanent magnets and solenoid coils fixed on the same magnetic yoke that acts as a magnetic flux concentrator. The magnetic field creates magnetization forces that guide functionalized paramagnetic microparticles through the volume of an analyte sample, in order to capture targeted pathogens. The presence of bacteria is sensed with an additional electrical impedance spectroscopy (EIS) module attached to the system, at high-frequency electrical fields. The magnetic field control is studied using mathematical modeling and numerical simulation in several geometry setups, coil excitation, and remanent flux density values.
Keywords: Magnetic actuation; Pathogen detection; Magnetic field; Numerical simulation